A super waterproof TPU film and preparation method thereof
The TPU film, utilizing a PDMS template and polyaniline@TiO2 composite, addresses the limitations of existing superhydrophobic TPU methods by achieving improved waterproofing and hydrophobicity suitable for fabrics and vehicle protection.
Patent Information
- Application Number
- CN202311649597.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-05
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-12-05
AI Technical Summary
Existing methods for creating superhydrophobic surfaces on TPU materials require harsh conditions or environmentally harmful substances, limiting their practical application.
A super waterproof TPU film is prepared by using a PDMS substrate with a micro-nano structure as a template, loading a polyaniline@TiO2 composite microsphere layer on the TPU surface, and modifying it with a dodecylbenzenesulfonic acid solution.
The resulting TPU film achieves enhanced waterproofing properties with a superhydrophobic effect, expanding its applicability to waterproof fabrics and vehicle protective films.
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, and in particular to an ultra-waterproof TPU film and a preparation method thereof. Background Art
[0002] Thermoplastic polyurethane elastomer (TPU) is a (AB)n type multi-block linear polymer. The A segment is composed of soft polymer diols, which provides extensibility for the TPU material and is called the soft segment; the B segment is composed of diisocyanate and small molecule diols, and its structure is rigid, which provides crystallinity and strength for the material and is called the hard segment. TPU materials have excellent mechanical properties such as high strength, high elasticity, high wear resistance and high flexibility, and are resistant to oil, solvents and general chemicals. These good properties make TPU widely used in many aspects such as medicine and health, cables, pipes, automobiles, clothing, shoes and hats, films and sheets. Among them, the new application of thermoplastic polyurethane in the clothing industry is that it can be made into a film attached to the fabric, giving users good protection and comfort.
[0003] Generally, there are two methods for preparing superhydrophobic surfaces: one is to construct a rough geometric structure on the surface of a hydrophobic material with low surface energy (contact angle greater than 90°); the other is to use low surface energy substances such as silicates, fluorides, etc. to modify the surface with a rough structure; to date, the superhydrophobic modification method of low surface energy substances such as silicone and fluorine-containing compounds is mainly used on textile fabrics. However, these methods either have harsh preparation conditions and require expensive raw materials, or use substances that are potentially dangerous to the environment or fur (such as organic fluorides), which greatly limits the practical application of this superhydrophobic technology. Summary of the invention
[0004] Technical problem to be solved: The purpose of the present invention is to provide an ultra-waterproof TPU film, which uses a PDMS substrate with a functional surface morphology of micro-nano structure as a template, and then loads polyaniline@TiO2, so that the micro-nano structure of the TPU surface is richer and the waterproof effect of TPU is improved.
[0005] Technical solution: An ultra-waterproof TPU film, which is composed of a wrinkled TPU film and a polyaniline / TiO2 composite microsphere layer attached to the surface of the TPU film.
[0006] The preparation method of the above-mentioned super waterproof TPU film comprises the following steps:
[0007] S1. Preparation of PDMS substrate: PDMS prepolymer and cross-linking agent were mixed in a mass ratio of 5-15:1, stirred evenly to obtain a prepolymer, spread the prepolymer on a glass plate and degassed, and then cured at 60-70° C. for 5-6 hours to obtain a PDMS substrate;
[0008] S2. Preparation of TPU solution: TPU was added to DMF, the solution was heated to swell, and then stirred until the TPU was completely dissolved, and allowed to stand for degassing to obtain a TPU solution;
[0009] S3. Preparation of PDMS / TPU double-layer membrane: Spin-coat a layer of TPU membrane on the surface of the PDMS substrate with TPU solution, and then heat it at 80-90°C to obtain a TPU membrane with a wrinkled surface morphology;
[0010] S4. Preparation of polyaniline@TiO2 composite microsphere layer: TiO2 is added to a hydrochloric acid ethanol solution, and ultrasonically dispersed to obtain a TiO2 suspension, and the TiO2 suspension is coated on a PDMS / TPU double-layer membrane soaked in hydrochloric acid, and dried, and then the PDMS / TPU double-layer membrane is placed in a hydrochloric acid solution containing aniline, and an ammonium persulfate hydrochloric acid solution is added to the hydrochloric acid solution containing aniline under ice bath conditions to initiate polymerization to obtain a polyaniline@TiO2 composite microsphere layer;
[0011] S5. Transfer of TPU film: prepare polyvinyl alcohol solution, cast it on the surface of polyaniline / TiO2 composite microsphere layer, dry and solidify at room temperature to obtain PDMS / TPU / polyaniline@TiO2 / PVA film, peel off TPU / polyaniline@TiO2 / PVA from PDMS substrate to obtain TPU / polyaniline@TiO2 / PVA film, place TPU / polyaniline@TiO2 / PVA film in water to dissolve PVA on the surface, and obtain TPU film;
[0012] S6. Preparation of super waterproof TPU film: The TPU film is immersed in a dodecylbenzenesulfonic acid solution for modification to obtain a super waterproof TPU film.
[0013] Preferably, in step S2, the mass volume ratio of TPU to DMF is 2-5:15-25 g / mL, and the swelling temperature is 80-90° C. Preferably, in step S3, the spin coating conditions are: a rotation speed of 3000-4000 rpm, a spin coating time of 20-30 s, and a TPU film thickness of 0.07-0.1 mm.
[0014] Preferably, in step S4, the concentration of the TiO2 suspension is 15-25wt%, the concentration of aniline is 0.1-0.2mol / L, the concentration of ammonium persulfate is 0.2-0.4mol / L, and the concentration of hydrochloric acid is 0.3-0.8mol / L.
[0015] Preferably, the concentration of polyvinyl alcohol in step S5 is 8-10 wt %.
[0016] Preferably, the concentration of the dodecylbenzenesulfonic acid solution in step S6 is 0.2-0.5 mol / L, and the modification time is 6-10 hours. Application of the above-mentioned super waterproof TPU film in waterproof fabrics and vehicle protective films.
[0017] Beneficial effects: The ultra-waterproof TPU film of the present invention has the following advantages:
[0018] 1. In the present invention, a PDMS substrate is used as a template. Since the PDMS surface has a functional surface morphology of a micro-nano structure, the TPU film obtained by spin coating the TPU solution on the PDMS surface also has the functional surface morphology of the micro-nano structure of PDMS. The micro-nano structure of the TPU surface can improve the waterproof effect of TPU;
[0019] 2. In order to further improve the waterproof effect of TPU, a layer of polyaniline@TiO2 composite microsphere layer is loaded on the surface of TPU. The general aniline is linear in the process of synthesizing polyaniline and cannot have a spherical shape. In the present invention, titanium dioxide is used as a template to prepare polyaniline micro-nanospheres, which can improve the roughness of the material surface;
[0020] 3. The TPU / polyaniline@TiO2 film is transferred from the PDMS using polyvinyl alcohol to obtain a TPU film with a complete surface loaded with a polyaniline@TiO2 composite microsphere layer. The TPU film with a surface loaded with a polyaniline@TiO2 composite microsphere layer is further treated with a dodecylbenzenesulfonic acid solution. The hydrophilic groups of the dodecylbenzenesulfonic acid are doped into the polyaniline molecular chain, and the hydrophobic groups are modified on the surface, finally obtaining a superhydrophobic TPU film. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments:
[0022] Example 1
[0023] An ultra-waterproof TPU film, the ultra-waterproof TPU film consisting of a wrinkled TPU film and a polyaniline / TiO2 composite microsphere layer attached to the surface of the TPU film;
[0024] The preparation method of the above-mentioned super waterproof TPU film comprises the following steps:
[0025] S1. Preparation of PDMS substrate: PDMS prepolymer and cross-linking agent were mixed in a mass ratio of 5:1, stirred evenly to obtain a prepolymer, spread the prepolymer on a glass plate and degassed, and then cured at 60° C. for 6 h to obtain a PDMS substrate;
[0026] S2. Preparation of TPU solution: TPU was added to DMF, the mass volume ratio of TPU and DMF was 2:15 g / mL, the solution was heated for swelling, the swelling temperature was 80°C, and then stirred until TPU was completely dissolved, and allowed to stand for degassing to obtain a TPU solution;
[0027] S3. Preparation of PDMS / TPU double-layer membrane: Spin-coat a layer of TPU membrane on the surface of the PDMS substrate with a TPU solution at a spinning speed of 4000 rpm and a spin-coating time of 20 s. The thickness of the TPU membrane is 0.07 mm, and then heated at 80°C to obtain a TPU membrane with a wrinkled surface morphology;
[0028] S4. Preparation of polyaniline@TiO2 composite microsphere layer: Add TiO2 with a concentration of 15wt% to a hydrochloric acid ethanol solution with a concentration of 0.8mol / L, disperse it evenly by ultrasonication to obtain a TiO2 suspension, apply the TiO2 suspension to a PDMS / TPU double-layer membrane soaked in hydrochloric acid, dry it, and then put the PDMS / TPU double-layer membrane into a hydrochloric acid solution containing aniline with a concentration of 0.1mol / L, the concentration of hydrochloric acid is 0.3mol / L, add a hydrochloric acid solution of ammonium persulfate with a concentration of 0.4mol / L to the hydrochloric acid solution containing aniline under ice bath conditions, the volume ratio is 1:1, and initiate polymerization to obtain a polyaniline@TiO2 composite microsphere layer;
[0029] S5. Transfer of TPU film: prepare a polyvinyl alcohol solution with a concentration of 8wt%, cast it on the surface of the polyaniline / TiO2 composite microsphere layer, dry and solidify it at room temperature to obtain a PDMS / TPU / polyaniline@TiO2 / PVA film, peel off the TPU / polyaniline@TiO2 / PVA from the PDMS substrate to obtain a TPU / polyaniline@TiO2 / PVA film, place the TPU / polyaniline@TiO2 / PVA film in water to dissolve the PVA on the surface, and obtain a TPU film;
[0030] S6. Preparation of super waterproof TPU film: The TPU film was immersed in a dodecylbenzenesulfonic acid solution with a concentration of 0.5 mol / L for modification. The modification time was 10 h to obtain a super waterproof TPU film.
[0031] Example 2
[0032] An ultra-waterproof TPU film, the ultra-waterproof TPU film consisting of a wrinkled TPU film and a polyaniline / TiO2 composite microsphere layer attached to the surface of the TPU film;
[0033] The preparation method of the above-mentioned super waterproof TPU film comprises the following steps:
[0034] S1. Preparation of PDMS substrate: PDMS prepolymer and cross-linking agent were mixed in a mass ratio of 15:1, stirred evenly to obtain a prepolymer, spread the prepolymer on a glass plate and degassed, and then cured at 70° C. for 5 h to obtain a PDMS substrate;
[0035] S2. Preparation of TPU solution: TPU was added to DMF, the mass volume ratio of TPU and DMF was 1:5 g / mL, the solution was heated for swelling, the swelling temperature was 90°C, and then stirred until TPU was completely dissolved, and allowed to stand for degassing to obtain TPU solution; S3. Preparation of PDMS / TPU double-layer membrane: TPU solution was spin-coated on the surface of PDMS substrate to form a layer of TPU membrane, the rotation speed was 3000 rpm, the spin-coating time was 30 s, the thickness of the TPU membrane was 0.1 mm, and then heated at 90°C to obtain a TPU membrane with a wrinkled surface;
[0036] S4. Preparation of polyaniline@TiO2 composite microsphere layer: Add TiO2 with a concentration of 25wt% to a hydrochloric acid ethanol solution with a concentration of 0.3mol / L, disperse it evenly by ultrasonication to obtain a TiO2 suspension, apply the TiO2 suspension to a PDMS / TPU double-layer membrane soaked in hydrochloric acid, dry it, and then put the PDMS / TPU double-layer membrane into a hydrochloric acid solution containing aniline with a concentration of 0.2mol / L, the concentration of hydrochloric acid is 0.8mol / L, add a hydrochloric acid solution of ammonium persulfate with a concentration of 0.2mol / L to the hydrochloric acid solution containing aniline under ice bath conditions, the volume ratio is 1:1, and initiate polymerization to obtain a polyaniline@TiO2 composite microsphere layer;
[0037] S5. Transfer of TPU film: prepare a polyvinyl alcohol solution with a concentration of 10wt%, cast it on the surface of the polyaniline / TiO2 composite microsphere layer, dry and solidify it at room temperature to obtain a PDMS / TPU / polyaniline@TiO2 / PVA film, peel off the TPU / polyaniline@TiO2 / PVA from the PDMS substrate to obtain a TPU / polyaniline@TiO2 / PVA film, place the TPU / polyaniline@TiO2 / PVA film in water to dissolve the PVA on the surface, and obtain a TPU film;
[0038] S6. Preparation of super waterproof TPU film: The TPU film was immersed in a dodecylbenzenesulfonic acid solution with a concentration of 0.2 mol / L for modification. The modification time was 10 h to obtain a super waterproof TPU film.
[0039] Example 3
[0040] An ultra-waterproof TPU film, the ultra-waterproof TPU film consisting of a wrinkled TPU film and a polyaniline / TiO2 composite microsphere layer attached to the surface of the TPU film;
[0041] The preparation method of the above-mentioned super waterproof TPU film comprises the following steps:
[0042] S1. Preparation of PDMS substrate: PDMS prepolymer and cross-linking agent were mixed in a mass ratio of 8:1, stirred evenly to obtain a prepolymer, spread the prepolymer on a glass plate and degassed, and then cured at 60° C. for 6 h to obtain a PDMS substrate;
[0043] S2. Preparation of TPU solution: TPU was added to DMF, the mass volume ratio of TPU to DMF was 2:11 g / mL, the solution was heated for swelling, the swelling temperature was 85°C, and then stirred until TPU was completely dissolved, and allowed to stand for degassing to obtain a TPU solution;
[0044] S3. Preparation of PDMS / TPU double-layer membrane: Spin-coat a layer of TPU membrane on the surface of the PDMS substrate with a TPU solution at a spinning speed of 3000 rpm and a spin-coating time of 30 s. The thickness of the TPU membrane is 0.1 mm, and then heated at 80°C to obtain a TPU membrane with a wrinkled surface.
[0045] S4. Preparation of polyaniline@TiO2 composite microsphere layer: Add TiO2 with a concentration of 18wt% to a hydrochloric acid ethanol solution with a concentration of 0.7mol / L, disperse it evenly by ultrasonication to obtain a TiO2 suspension, apply the TiO2 suspension to a PDMS / TPU double-layer membrane soaked in hydrochloric acid, dry it, and then put the PDMS / TPU double-layer membrane into a hydrochloric acid solution containing aniline with a concentration of 0.15mol / L, the concentration of hydrochloric acid is 0.5mol / L, add a hydrochloric acid solution of ammonium persulfate with a concentration of 0.4mol / L to the hydrochloric acid solution containing aniline under ice bath conditions, the volume ratio is 1:1, and initiate polymerization to obtain a polyaniline@TiO2 composite microsphere layer;
[0046] S5. Transfer of TPU film: prepare a polyvinyl alcohol solution with a concentration of 10wt%, cast it on the surface of the polyaniline / TiO2 composite microsphere layer, dry and solidify it at room temperature to obtain a PDMS / TPU / polyaniline@TiO2 / PVA film, peel off the TPU / polyaniline@TiO2 / PVA from the PDMS substrate to obtain a TPU / polyaniline@TiO2 / PVA film, place the TPU / polyaniline@TiO2 / PVA film in water to dissolve the PVA on the surface, and obtain a TPU film;
[0047] S6. Preparation of super waterproof TPU film: The TPU film was immersed in a dodecylbenzenesulfonic acid solution with a concentration of 0.3 mol / L for modification. The modification time was 7 hours to obtain a super waterproof TPU film.
[0048] Example 4
[0049] An ultra-waterproof TPU film, the ultra-waterproof TPU film consisting of a wrinkled TPU film and a polyaniline / TiO2 composite microsphere layer attached to the surface of the TPU film;
[0050] The preparation method of the above-mentioned super waterproof TPU film comprises the following steps:
[0051] S1. Preparation of PDMS substrate: PDMS prepolymer and cross-linking agent were mixed in a mass ratio of 12:1, stirred evenly to obtain a prepolymer, spread the prepolymer on a glass plate and degassed, and then cured at 70° C. for 5 h to obtain a PDMS substrate;
[0052] S2. Preparation of TPU solution: TPU was added to DMF, the mass volume ratio of TPU and DMF was 1:6 g / mL, the solution was heated for swelling, the swelling temperature was 80°C, and then stirred until TPU was completely dissolved, and allowed to stand for degassing to obtain TPU solution; S3. Preparation of PDMS / TPU double-layer membrane: TPU solution was spin-coated on the surface of PDMS substrate to form a layer of TPU membrane, the rotation speed was 3500 rpm, the spin-coating time was 30 s, the thickness of the TPU membrane was 0.08 mm, and then heated at 90°C to obtain a TPU membrane with a wrinkled surface;
[0053] S4. Preparation of polyaniline@TiO2 composite microsphere layer: Add TiO2 with a concentration of 22wt% to a hydrochloric acid ethanol solution with a concentration of 0.5mol / L, disperse it evenly by ultrasonication to obtain a TiO2 suspension, apply the TiO2 suspension to a PDMS / TPU double-layer membrane soaked in hydrochloric acid, dry it, and then put the PDMS / TPU double-layer membrane into a hydrochloric acid solution containing aniline with a concentration of 0.18mol / L, the concentration of hydrochloric acid is 0.7mol / L, add a hydrochloric acid solution of ammonium persulfate with a concentration of 0.3mol / L to the hydrochloric acid solution containing aniline under ice bath conditions, the volume ratio is 1:1, and initiate polymerization to obtain a polyaniline@TiO2 composite microsphere layer;
[0054] S5. Transfer of TPU film: prepare a polyvinyl alcohol solution with a concentration of 10wt%, cast it on the surface of the polyaniline / TiO2 composite microsphere layer, dry and solidify it at room temperature to obtain a PDMS / TPU / polyaniline@TiO2 / PVA film, peel off the TPU / polyaniline@TiO2 / PVA from the PDMS substrate to obtain a TPU / polyaniline@TiO2 / PVA film, place the TPU / polyaniline@TiO2 / PVA film in water to dissolve the PVA on the surface, and obtain a TPU film;
[0055] S6. Preparation of super waterproof TPU film: The TPU film was immersed in a dodecylbenzenesulfonic acid solution with a concentration of 0.4 mol / L for modification. The modification time was 9 hours to obtain a super waterproof TPU film.
[0056] Example 5
[0057] An ultra-waterproof TPU film, the ultra-waterproof TPU film consisting of a wrinkled TPU film and a polyaniline / TiO2 composite microsphere layer attached to the surface of the TPU film;
[0058] The preparation method of the above-mentioned super waterproof TPU film comprises the following steps:
[0059] S1. Preparation of PDMS substrate: PDMS prepolymer and cross-linking agent were mixed in a mass ratio of 10:1, stirred evenly to obtain a prepolymer, spread the prepolymer on a glass plate and degassed, and then cured at 70° C. for 5 h to obtain a PDMS substrate;
[0060] S2. Preparation of TPU solution: TPU was added to DMF, the mass volume ratio of TPU and DMF was 1:4 g / mL, the solution was heated for swelling, the swelling temperature was 85°C, and then stirred until TPU was completely dissolved, and allowed to stand for degassing to obtain TPU solution; S3. Preparation of PDMS / TPU double-layer membrane: TPU solution was spin-coated on the surface of PDMS substrate to form a layer of TPU membrane, the rotation speed was 3200 rpm, the spin-coating time was 25 s, the thickness of the TPU membrane was 0.1 mm, and then heated at 90°C to obtain a TPU membrane with a wrinkled surface;
[0061] S4. Preparation of polyaniline@TiO2 composite microsphere layer: Add TiO2 with a concentration of 18wt% to a hydrochloric acid ethanol solution with a concentration of 0.7mol / L, disperse it evenly by ultrasonication to obtain a TiO2 suspension, apply the TiO2 suspension to a PDMS / TPU double-layer membrane soaked in hydrochloric acid, dry it, and then put the PDMS / TPU double-layer membrane into a hydrochloric acid solution containing aniline with a concentration of 0.16mol / L, the concentration of hydrochloric acid is 0.5mol / L, add a hydrochloric acid solution of ammonium persulfate with a concentration of 0.35mol / L to the hydrochloric acid solution containing aniline under ice bath conditions, the volume ratio is 1:1, and initiate polymerization to obtain a polyaniline@TiO2 composite microsphere layer;
[0062] S5. Transfer of TPU film: prepare a polyvinyl alcohol solution with a concentration of 10wt%, cast it on the surface of the polyaniline / TiO2 composite microsphere layer, dry and solidify it at room temperature to obtain a PDMS / TPU / polyaniline@TiO2 / PVA film, peel off the TPU / polyaniline@TiO2 / PVA from the PDMS substrate to obtain a TPU / polyaniline@TiO2 / PVA film, place the TPU / polyaniline@TiO2 / PVA film in water to dissolve the PVA on the surface, and obtain a TPU film;
[0063] S6. Preparation of super waterproof TPU film: The TPU film was immersed in a dodecylbenzenesulfonic acid solution with a concentration of 0.4 mol / L for modification. The modification time was 8 hours to obtain a super waterproof TPU film.
[0064] Comparative Example 1
[0065] An ultra-waterproof TPU film, the ultra-waterproof TPU film consisting of a wrinkled TPU film and a polyaniline / TiO2 composite microsphere layer attached to the surface of the TPU film;
[0066] The preparation method of the above-mentioned super waterproof TPU film comprises the following steps:
[0067] S1. Preparation of PDMS substrate: PDMS prepolymer and cross-linking agent were mixed in a mass ratio of 15:1, stirred evenly to obtain a prepolymer, spread the prepolymer on a glass plate and degassed, and then cured at 70° C. for 5 h to obtain a PDMS substrate;
[0068] S2. Preparation of TPU solution: TPU was added to DMF, the mass volume ratio of TPU and DMF was 1:5 g / mL, the solution was heated for swelling, the swelling temperature was 90°C, and then stirred until TPU was completely dissolved, and allowed to stand for degassing to obtain TPU solution; S3. Preparation of PDMS / TPU double-layer membrane: TPU solution was spin-coated on the surface of PDMS substrate to form a layer of TPU membrane, the rotation speed was 3000 rpm, the spin-coating time was 30 s, the thickness of the TPU membrane was 0.1 mm, and then heated at 90°C to obtain a TPU membrane with a wrinkled surface;
[0069] S4. Preparation of polyaniline@TiO2 composite microsphere layer: Add TiO2 with a concentration of 25wt% to a hydrochloric acid ethanol solution with a concentration of 0.3mol / L, disperse it evenly by ultrasonication to obtain a TiO2 suspension, apply the TiO2 suspension to a PDMS / TPU double-layer membrane soaked in hydrochloric acid, dry it, and then put the PDMS / TPU double-layer membrane into a hydrochloric acid solution containing aniline with a concentration of 0.2mol / L, the concentration of hydrochloric acid is 0.8mol / L, add a hydrochloric acid solution of ammonium persulfate with a concentration of 0.2mol / L to the hydrochloric acid solution containing aniline under ice bath conditions, the volume ratio is 1:1, and initiate polymerization to obtain a polyaniline@TiO2 composite microsphere layer;
[0070] S5. Transfer of TPU film: prepare a polyvinyl alcohol solution with a concentration of 10wt%, pour it on the surface of the polyaniline / TiO2 composite microsphere layer, dry and solidify it at room temperature to obtain a PDMS / TPU / polyaniline@TiO2 / PVA film, peel off the TPU / polyaniline@TiO2 / PVA from the PDMS substrate to obtain a TPU / polyaniline@TiO2 / PVA film, place the TPU / polyaniline@TiO2 / PVA film in water to dissolve the PVA on the surface to obtain a TPU film.
[0071] Comparative Example 2
[0072] A super waterproof TPU film, the super waterproof TPU film is composed of a wrinkled TPU film and a waterproof layer attached to the surface of the TPU film; the preparation method of the super waterproof TPU film comprises the following steps:
[0073] S1. Preparation of PDMS substrate: PDMS prepolymer and cross-linking agent were mixed in a mass ratio of 12:1, stirred evenly to obtain a prepolymer, spread the prepolymer on a glass plate and degassed, and then cured at 70° C. for 5 h to obtain a PDMS substrate;
[0074] S2. Preparation of TPU solution: TPU was added to DMF, the mass volume ratio of TPU and DMF was 1:6 g / mL, the solution was heated for swelling, the swelling temperature was 80°C, and then stirred until TPU was completely dissolved, and allowed to stand for degassing to obtain TPU solution; S3. Preparation of PDMS / TPU double-layer membrane: TPU solution was spin-coated on the surface of PDMS substrate to form a layer of TPU membrane, the rotation speed was 3500 rpm, the spin-coating time was 30 s, the thickness of the TPU membrane was 0.08 mm, and then heated at 90°C to obtain a TPU membrane with a wrinkled surface;
[0075] S4. Preparation of waterproof TPU film: The TPU film was immersed in a dodecylbenzenesulfonic acid solution with a concentration of 0.4 mol / L for modification. The modification time was 9 hours to obtain an ultra-waterproof TPU film.
[0076] Comparative Example 3
[0077] The invention discloses an ultra-waterproof TPU film, which is composed of a wrinkled TPU film and a polyaniline / TiO2 composite microsphere layer attached to the surface of the TPU film.
[0078] The preparation method of the above-mentioned super waterproof TPU film comprises the following steps:
[0079] S1. Preparation of PDMS substrate: PDMS prepolymer and cross-linking agent were mixed in a mass ratio of 10:1, stirred evenly to obtain a prepolymer, spread the prepolymer on a glass plate and degassed, and then cured at 70° C. for 5 h to obtain a PDMS substrate;
[0080] S2. Preparation of TPU solution: TPU was added to DMF, the mass volume ratio of TPU and DMF was 1:4 g / mL, the solution was heated for swelling, the swelling temperature was 85°C, and then stirred until TPU was completely dissolved, and allowed to stand for degassing to obtain TPU solution; S3. Preparation of PDMS / TPU double-layer membrane: TPU solution was spin-coated on the surface of PDMS substrate to form a layer of TPU membrane, the rotation speed was 3200 rpm, the spin-coating time was 25 s, the thickness of the TPU membrane was 0.1 mm, and then heated at 90°C to obtain a TPU membrane with a wrinkled surface;
[0081] S4. Preparation of polyaniline layer: The PDMS / TPU double-layer film was placed in a hydrochloric acid solution containing aniline at a concentration of 0.16 mol / L, the concentration of the hydrochloric acid was 0.5 mol / L, and a hydrochloric acid solution of ammonium persulfate at a concentration of 0.35 mol / L was added to the hydrochloric acid solution containing aniline in an ice bath at a volume ratio of 1:1 to initiate polymerization to obtain a polyaniline layer;
[0082] S5. Transfer of TPU film: prepare a polyvinyl alcohol solution with a concentration of 10 wt%, cast it on the surface of the polyaniline layer, dry and solidify it at room temperature to obtain a PDMS / TPU / polyaniline / PVA film, peel off the TPU / polyaniline / PVA from the PDMS substrate to obtain a TPU / polyaniline / PVA film, place the TPU / polyaniline / PVA film in water to dissolve the PVA on the surface, and obtain a TPU film;
[0083] S6. Preparation of super waterproof TPU film: The TPU film was immersed in a dodecylbenzenesulfonic acid solution with a concentration of 0.4 mol / L for modification. The modification time was 8 hours to obtain a super waterproof TPU film.
[0084] Performance Test:
[0085] Water contact angle / ° Example 1 164.5 Example 2 160.8 Example 3 163.9 Example 4 166.4 Example 5 165.1 Comparative Example 1 150.8 Comparative Example 2 130.9 Comparative Example 3 125.4
[0086] It can be seen from the above table that the morphology of polyaniline on the surface of TPU film has a great influence on the water contact angle. The use of polyaniline loaded on the TiO2 surface gives the TPU surface more complex microscopic morphology, which can improve the hydrophobic properties of the film, prepare super-hydrophobic films, and expand the application range of TPU.
[0087] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A super waterproof TPU film, characterized in that: The super waterproof TPU film is composed of a wrinkled TPU film and a polyaniline / TiO2 composite microsphere layer attached to the surface of the TPU film; The method for preparing the ultra-waterproof TPU film comprises the following steps: S1. Preparation of PDMS substrate: PDMS prepolymer and cross-linking agent are mixed in a mass ratio of 5-15:1, stirred evenly to obtain a prepolymer, the prepolymer is spread on a glass plate and degassed, and then cured at 60-70° C. for 5-6 hours to obtain a PDMS substrate; S2. Preparation of TPU solution: TPU was added to DMF, the mass volume ratio of TPU and DMF was 2-5:15-25 g / mL, the solution was heated to swell, and then stirred until the TPU was completely dissolved, and allowed to stand for degassing to obtain a TPU solution; S3. Preparation of PDMS / TPU double-layer membrane: Spin-coat a TPU film on the surface of the PDMS substrate using a TPU solution, the thickness of the TPU film is 0.07-0.1 mm, and then heat it at 80-90°C to obtain a TPU film with a wrinkled surface; S4. Preparation of polyaniline@TiO2 composite microsphere layer: TiO2 is added to a hydrochloric acid ethanol solution, and ultrasonically dispersed to obtain a TiO2 suspension with a concentration of 15-25wt%, and the TiO2 suspension is coated on a PDMS / TPU double-layer membrane soaked in hydrochloric acid, and dried, and then the PDMS / TPU double-layer membrane is placed in a hydrochloric acid solution of aniline with a concentration of 0.1-0.2mol / L, and the concentration of hydrochloric acid is 0.3-0.8mol / L. Under ice bath conditions, a hydrochloric acid solution of ammonium persulfate with a concentration of 0.2-0.4mol / L is added to the hydrochloric acid solution containing aniline to initiate polymerization to obtain a polyaniline@TiO2 composite microsphere layer; S5. Transfer of TPU film: prepare polyvinyl alcohol solution, cast it on the surface of polyaniline / TiO2 composite microsphere layer, dry and solidify at room temperature to obtain PDMS / TPU / polyaniline@TiO2 / PVA film, peel off TPU / polyaniline@TiO2 / PVA from PDMS substrate to obtain TPU / polyaniline@TiO2 / PVA film, place TPU / polyaniline@TiO2 / PVA film in water to dissolve PVA on the surface, and obtain TPU film; S6. Preparation of super waterproof TPU film: The TPU film is immersed in a dodecylbenzenesulfonic acid solution for modification to obtain a super waterproof TPU film.
2. The ultra-waterproof TPU film according to claim 1, characterized in that: The swelling temperature in step S2 is 80-90°C.
3. The ultra-waterproof TPU film according to claim 1, characterized in that: The spin coating conditions in step S3 are: a rotation speed of 3000-4000 rpm and a spin coating time of 20-30 s.
4. The ultra-waterproof TPU film according to claim 1, characterized in that: The concentration of polyvinyl alcohol in step S5 is 8-10 wt %.
5. The ultra-waterproof TPU film according to claim 1, characterized in that: The concentration of the dodecylbenzenesulfonic acid solution in step S6 is 0.2-0.5 mol / L, and the modification time is 6-10 h.
6. Application of the super waterproof TPU film as claimed in claim 1 in waterproof fabrics and vehicle protective films.
Citation Information
Patent Citations
A method of preparing free surface-patterned polypyrrole film
CN106916325A
Preparation method for polyurethane nano zinc oxide super-hydrophobic coating
CN111842090A
Preparation method of durable super-hydrophobic micro-droplet self-cleaning coating based on polyaniline / attapulgite
CN114874675A
TPU (thermoplastic polyurethane) material as well as preparation method and application thereof
CN116854977A
Superhydrophobic membranes and methods of making and using same
US20230191339A1